Senadin Lavić "Leksikon socioloških pojmova" / Senadin Lavić 'Lexicon of Sociological Terms' - Osmić, Amer (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
This text deals with Senadin Lavić : 'Lexicon of Sociological Terms'.